CHALLENGES FACING THE REALIZATION OF MILLENNIUM DEVELOPMENT GOALS (MDG`s) IN EDUCATIONAL REFORM IN NIGERIA - Okeshola, Folshade B. (European Scientific Journal, ESJ, 2012)
The importance and linkage of education to the development of any society is well known. It is in recognition of this importance that the international community and governments all over the world have made commitments for citizens to have access to education. The delivery of education in Nigeria has suffered from years of neglect, compounded by inadequate attention to policy frameworks within the sector. The implementation of Millennium Development Goals (MDGs) is affected by corruption, gross inefficiency, wastefulness and duplication of projects in the same areas by the Federal government and donor agencies. This paper therefore examines the challenges facing the realization of MDGs in 2015 and what need to be done in order to achieve the set target for quality education in Nigeria.